Local Development Effect of Sports Facilities and Sports Teams: Case Studies Using Synthetic Control Method. (February 2019) - Islam, Muhammad Q.
Studies of the economic benefit of sports franchises to local economies typically utilize panel regression procedures to estimate the effect on variables of interest. An alternative to regression-type estimation is to adopt a case study approach utilizing the synthetic control method. We utilize this approach to study the effect of the National Football League (NFL) expansion into three cities. Specifically, we ask, how the presence of an NFL team in selected cities affected the time path of employment growth in those cities. Results reinforce the dominant view that presence of a sports franchise does not significantly affect the time path of employment.